The Existence and Persistence of Cycles in a Non-linear Model: Kaldor's 1940 Model Re-examined - Chang, W. W.; Smyth, D. J. (Review of Economic Studies, 1971)
Journal Article The Existence and Persistence of Cycles in a Non-linear Model: Kaldor's 1940 Model Re-examined Get access W. W. Chang, W. W. Chang State University of New York at Buffalo Search for other works by this author on: Oxford Academic Google Scholar D. J. Smyth D. J. Smyth Claremont Graduate School Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 38, Issue 1, January 1971, Pages 37–44, https://doi.org/10.2307/2296620 Published: 01 January 1971